2023
DOI: 10.1021/acsomega.2c07191
|View full text |Cite
|
Sign up to set email alerts
|

Dealloying Synthesis of Bimetallic (Au–Pd)/CeO2 Catalysts for CO Oxidation

Abstract: The nanorod-structured (Au−Pd)/CeO 2 catalysts with different Au/Pd ratios were prepared from Al−Ce−Au−Pd precursor alloys through combined dealloying and calcination treatment. XRD, SEM, TEM, XPS, Raman spectroscopy, and N 2 adsorption−desorption measurements were applied to test the structure and physicochemical properties of samples. Catalytic evaluation results imply that the (Pd 0.15 −Au 0.15 )/CeO 2 catalyst calcined at 500 °C possesses optimal catalytic activity for CO oxidation when compared with other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…105 In addition, the bimetallic catalysts typically exhibit better properties when compared with the constituent individual metals due to the optimized geometric and electronic properties of active sites caused by the synergistic effects in bimetallic catalysts. Wang et al 106 prepared the nanorod-shaped (Au–Pd)/CeO 2 catalysts which possess the interspersed nanorod structure with nanopores distributed among them. By rationally adjusting the Pd/Au ratio, the achieved (Pd 0.15 –Au 0.15 )/CeO 2 exhibits excellent catalytic activity for CO oxidation with T 50 and T 99 as low as 50 and 85 °C, respectively.…”
Section: Application Of Cerium-based Oxide Catalysts To Catalytic Eli...mentioning
confidence: 99%
“…105 In addition, the bimetallic catalysts typically exhibit better properties when compared with the constituent individual metals due to the optimized geometric and electronic properties of active sites caused by the synergistic effects in bimetallic catalysts. Wang et al 106 prepared the nanorod-shaped (Au–Pd)/CeO 2 catalysts which possess the interspersed nanorod structure with nanopores distributed among them. By rationally adjusting the Pd/Au ratio, the achieved (Pd 0.15 –Au 0.15 )/CeO 2 exhibits excellent catalytic activity for CO oxidation with T 50 and T 99 as low as 50 and 85 °C, respectively.…”
Section: Application Of Cerium-based Oxide Catalysts To Catalytic Eli...mentioning
confidence: 99%
“…[23] Cerium dioxide (CeO 2 ) has been extensively used as supporter for Au NPs in oxidation reaction due to its outstanding defect property and oxygen storage capacity, and researches shown that the catalytic performance was directly employed by V O of CeO 2 for catalysts. [24,25] Herein, we synthesized AuÀ Pd loaded on CeO 2 by the combining method of chemical reduction and photo-deposition. Catalysts AuPd/CeO 2 exhibited the outgoing oxidize activity for the production of FDCA from HMF at a mild condition.…”
Section: Introductionmentioning
confidence: 99%